Progress in chemical toxicology. - Stolman, Abraham, 1908- (Academic Press, 1967)
Progress in Chemical Toxicology, Volume 3 explores the developments in methods and instrumentation for toxicological analyses. This book is composed of eight chapters, and begins with a description of the pharmacologic and physiologic effects of aliphatic alcohols. The succeeding chapter deals with the methods of analysis of various volatile poisons, such as halogenated aliphatic compounds, aromatic hydrocarbons, and acid compounds. A chapter focuses on the methods of determination and classic procedures for carbon monoxide analysis in breath and blood. These topics are followed by discussions.